Health & Life: A tribute to the late Edmundo Granda Ugalde - Zaida Betancourt (Social Medicine Publication Group, 2024)
At the initiative of several Ecuadorian organizations - the National Council of Health (CONASA), the University of Cuenca, the National University of Loja, and the National Council of Higher Education (CONESUP) - and with the collaboration of both the Pan-American Health Organization (PAHO) and the Latin American Social Medicine Association Social (ALAMES), we are publishing the selected writings of Edmundo Granda as well as a volume of tributes.